2016
DOI: 10.1177/0194599816633457
|View full text |Cite
|
Sign up to set email alerts
|

Oral Antibiotic Use for Otitis Media with Effusion

Abstract: Oral antibiotics continue to be administered in children with OME in the absence of acute infection, with risk varying by location of service. There is a potential opportunity for quality improvement through reducing antibiotic administration for pediatric OME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Although antibiotic treatment is not recommended in the current guidelines, studies have shown that a diagnosis of OME is often followed by the prescription of a course of oral antibiotics – especially in the emergency room, more than in ENT departments (Roditi et al., 2016). For example, some centres prescribe treatment with macrolide antibiotics if OME is combined with rhinosinusitis, since the latter is a trigger for OME.…”
Section: Treatmentsmentioning
confidence: 99%
“…Although antibiotic treatment is not recommended in the current guidelines, studies have shown that a diagnosis of OME is often followed by the prescription of a course of oral antibiotics – especially in the emergency room, more than in ENT departments (Roditi et al., 2016). For example, some centres prescribe treatment with macrolide antibiotics if OME is combined with rhinosinusitis, since the latter is a trigger for OME.…”
Section: Treatmentsmentioning
confidence: 99%
“…In the studies that compared the practices of different types of clinicians, substantially higher adherence to guideline recommendations was displayed by otolaryngologists when compared to nonotolaryngologists, particularly for the recommendations in the Otitis Media with Effusion, Adult Sinusitis, and Sudden Hearing Loss guidelines ( Tables 2 , 5 , and 6 ). 16,22-27 Table 2 shows that adherence to the Otitis Media with Effusion guideline is high for otolaryngologists and low for nonotolaryngology clinicians. The potentially inappropriate (and not recommended) use of medical treatments such as intranasal steroids (odds ratio [OR], 3.58; 95% confidence interval [CI], 1.60-8.01), oral antihistamines (OR, 3.53; 95% CI, 1.62-7.71), and oral antibiotics (OR, 6.24; 95% CI: 4.17-9.39) was associated with encounters with nonotolaryngologists but not with otolaryngologists.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies that compared the practices of different types of clinicians, substantially higher adherence to guideline recommendations was displayed by otolaryngologists when compared to nonotolaryngologists, particularly for the (text continues on p. 641) recommendations in the Otitis Media with Effusion, Adult Sinusitis, and Sudden Hearing Loss guidelines ( Tables 2, 5, and 6). 16,[22][23][24][25][26][27] 22,24,25 Potentially unindicated prescriptions were especially common in the emergency department setting. 22,24…”
Section: Comparison Of Clinician and Setting Typementioning
confidence: 99%
See 1 more Smart Citation
“…An ongoing program during preschool age could in fact result in additional public health benefits: it would allow a reduction of family mobility in accessing to more expensive audiologic evaluations. Moreover, a self-help diagnosis would favor a more aware and appropriate prescription of antibiotic therapy in case of otitis media (16), possibly contributing to the strategies of the national plan against antimicrobial resistance. Ultimately, a better triage of children with HI would allow a more targeted referral of OMEs that require a surgical decision, with further reduction in direct and indirect surveillance costs.…”
Section: Discussionmentioning
confidence: 99%